Ultrasensitive nucleic acid detection based on phosphorothioated hairpin-assisted isothermal amplification - Yujin Jung (Nature Portfolio, 2021)
Abstract Herein, we describe a phosphorothioated hairpin-assisted isothermal amplification (PHAmp) method for detection of a target nucleic acid. The hairpin probe (HP) is designed to contain a 5′ phosphorothioate (PS)-modified overhang, a target recognition site, and a 3′ self-priming (SP) region. Upon binding to the target nucleic acid, the HP opens and the SP region is rearranged to serve as a primer. The subsequent process of strand displacement DNA synthesis recycles the bound target to open another HP and produces an extended HP (EP) with a PS-DNA/DNA duplex at the end, which would be readily denatured due to its reduced thermal stability. The trigger then binds to the denatured 3′ end of the EP and is extended, producing an intermediate double-stranded (ds) DNA product (IP). The trigger also binds to the denatured 3′ end of the IP, and its extension produces the final dsDNA product along with concomitant displacement and recycling of EP. By monitoring the dsDNA products, the target nucleic acid can be identified down to 0.29 fM with a wide dynamic range from 1 nM to 1 fM yielding an excellent specificity to discriminate even a single base-mismatched target. The unique design principle could provide new insights into the development of novel isothermal amplification methods for nucleic acid detection.